PENINGKATAN PARTISIPASI MASYARAKAT DALAM PENGELOLAAN POTENSI DESA BERBASIS IPTEK DI DESA BALUK - Atmika, I.K. A.; Suriadi, I.G.A.K.; Subagia, I.D.G.A. (Buletin Udayana Mengabdi, 2018)
The themes of the KKN-PPM program in Baluk village are: Empowerment and Improvement of community participation in the management of the potential of science and technology-based villages to Mandiri villages through programs such as: public health programs: household sanitation counseling and counseling of clean and healthy lifestyle in children. school children. Environmental program: reforestation activities in the area along the village road. Increased productivity of community / business groups in the production of soy milk through the introduction and application of blender machine technology. Cost-efficiency with the introduction and application of biogas / biogas portable biogas technology with the use of cow dung for a day-to-day energy source. Increased public participation in all KKN-PPM activities. Increased community self-reliance in continuing every program that has been accompanied during KKN-PPM activities. Method of implementation of activities is divided into three stages. The first stage is preparation and briefing, second phase of implementation of activities in the field, and third stage evaluation and monitoring for correction and refinement of program sustainability. Preparatory phase begins with field supervisors and students with the village apparatus and community leaders to determine the priority scale of activities based on the conditions and potentials that exist in the community, this activity was held on July 20, 2017. The implementation of activities carried out with counseling and practice in the field , as well as mentoring by students participating KKN during the field. The dedication activity is held for one month starting from July 22, 2017 until August 27, 2017. While the third stage is the evaluation and monitoring conducted by the team of field supervisors and coordinators of KKN to see the impact and sustainability of programs that have been implemented.